Effectiveness of Fluoroquinolone Prophylaxis for High-risk Patients with Neutropenia in Hematopoietic Stem Cell Transplant Recipients in the Era of Rising Gram-negative Bacterial Resistance. (4th October 2017) - Hanna, Zachary; Abrencillo, Rodeo; Jayaprakash, Rachna; Del Busto, Ramon; Abreu-Lanfranco, Odaliz; Alangaden, George; Janakiraman, Nalini; Ramesh, Mayur
Abstract: Background: Fluoroquinolone prophylaxis (FQP) for anticipated prolonged and profound neutropenia (ANC ≤100 cells/mm 3 for >7 days) in hematopoietic stem cell transplant (HSCT) recipients has been supported by 2010 updated guidelines from IDSA. But, this recommendation is based on data from clinical trials well over a decade ago. In the era of rising Gram-negative bacterial (GNB) resistance, the continued role of FQP in this setting in reducing GNB blood stream infections (BSI) and subsequent development of GNB FQ resistance needs to be addressed. We sought to study this in a large cohort of HSCT recipients over a decade. Methods: Retrospective were collected from a large academic center in Detroit, USA from all patients who underwent HSCT and received FQP from 1999 to 2011. The patients were grouped into early years (EY) (1999–2004) and later years (LY) (2008–2011) to account for changes in GNB resistance over time. Demographic data, breakthrough bacteremia during neutropenic period and all subsequent positive cultures (blood, urine, sputum, or wound) for 6 months after HSCT were collected. Data from the groups were compared for incidence of BSI and development of GNB resistance. Results: A total of 243 HSCT recipients (early 95, late 148) were included for analysis. Mean age was 46.3 ± 12.5 years in EY group and 53.5 ± 13.7 in LY group (P <0.001). All patients received FQP until ANC was >500 cells/mm 3 (ciprofloxacin 238, levofloxacin 5). Mean duration of neutropenia was 14.6 ± 9.5 days in the EY group vs. 11.8 ± 8.6 in the LY group ( P  < 0.001). There was no statistically significant difference in the incidence of GNB BSI between the two groups (early 1 vs. late 5, P = 0.408). Analysis of data based on the absence ( n = 237) or presence ( n = 6) of GNB BSI revealed no statistically significant difference among age, neutropenic days and underlying diagnosis. No case of Pseudomonas BSI was noted in the entire cohort. There was no change in the incidence rates of GNB BSI over the study period. GNB resistance for FQ over the subsequent 6 months from HSCT remained unchanged (5/27 GNB positive cultures; 19%) compared with baseline in this population. Conclusion: Appropriate FQP for high-risk HSCT patients with neutropenia continues to be effective in reducing GNB BSI without significant impact on GNB resistance to FQ. Disclosures: All authors: No reported disclosures.